A new procedure, free from human assessment, that automatically grades some facial skin signs in men from selfie pictures. Application to changes induced by a severe aerial chronic urban pollution. (20th March 2020) - Zhang, Y.; Jiang, R.; Kezele, I.; Flament, F.; Elmozino, E.; Zhang, J.; Ye, C.; Amar, D.; Coquide, J.; Dwivedi, S.; Sarda‐Dutilh, L.; Arcin, V.; et al.
Abstract: Objective: These were two folds: at first, to develop an automatic grading system specifically dedicated to some facial signs of men, similar to the one previously validated on women of different ethnic ancestry and second, to assess its potential in detecting and grading the possible impacts of a severe aerial urban pollution on some facial signs of Chinese men. Methods: In both studies, selfie images were obtained from differently aged men. Nine facial signs were automatically graded through a specific A.I‐based algorithm and clinically assessed by a panel of experts and dermatologists. Selfie pictures were taken from individual smartphones of variable optical properties. The first study, designed for developing an automatic grading system, involved three comparable cohorts of men from three different regional ancestries (African, Asian, Caucasian, 110 each) the selfie images of which were acquired under four different lighting conditions. As a second use case study, the facial signs of two cohorts of Chinese men (101 and 100, each), differently aged, regularly exposed to very different aerial urban pollution conditions (UP) were analysed by the same algorithm, selfies being taken under only one lighting condition. Results: ‐ The new automatic grading system of facial signs suits well to men, showing comparable results than that the one dedicated to women and provides data in close agreement with experts' assessments. ‐ In both cases (expert's or automatic methodology), the accuracy of the scores appeared ethnic‐dependent. ‐ The applied case confirmed previous results obtained clinically, that is, that many facial signs were found of an increased severity among men exposed to a severe urban pollution, as compared to those living in a less polluted city. ‐ In both studies, statistical agreements between the automatic grading system and expert's assessments were reached. In some facial signs, the automatic grading system seems offering a slightly better accuracy than the assessments made by the experts. Conclusion: Apart from some minor limitations, this A.I‐based automatic grading system, free from human intervention, performed as well as the one previously developed in women, in close agreement with expert's assessments. In epidemiological studies, this system offers an easy, fast, affordable and confidential approach in the detection and quantification of male facial signs. Abstract : Examples of four selfie images self‐taken by an Asian man under 4 different lighting conditions. Résumé: Objectif: Il était double: (i) de développer d'un système automatique de scorage spécifique de plusieurs signes faciaux pour les hommes, similaire à celui précédemment validé sur des femmes de différentes origines. Et (ii), de jauger ses capacités pour la détection et l'évaluation des possibles impacts d'une pollution aérienne urbaine sévère sur le visage d'hommes chinois. Méthodes: Dans chacune des deux études des images de type selfies d'hommes de différents âges ont été obtenues. Neuf signes faciaux ont été automatiquement évalués grâce à un algorithme spécifique basé sur l'Intelligence Artificielle (IA) puis scorés cliniquement par un panel d'experts et de dermatologues. Des selfies ont été acquis à partir de téléphones portables individuels possédants des optiques et des résolutions différentes. L'étude N°1, conçue pour développer un système de scorage automatique du visage, a regroupé trois cohortes comparables d'hommes d'origines géographiques différentes (Africain, Asiatique et Caucasien, 110 volontaires par ethnies) et a requis l'acquisition sous 4 conditions d'éclairage. L'étude N°2, comme cas pratique, a nécessité le recrutement de deux cohortes d'hommes chinois d'âges différents (101 et 101 volontaires chacune) exposés régulièrement à de très différentes conditions de pollution aérienne urbaine et pour lesquels des selfies ont été enregistrés sous une seule condition d'éclairage. Résultats: ‐ Le nouveau système de scorage automatique de signes faciaux des hommes performe de manière satisfaisante et montre des résultats comparables à celui précédemment conçu pour les femmes et donne des mesures très proches des évaluations cliniques des experts et dermatologues. ‐ Dans les deux cas (experts ou mesures automatiques), l'acuité des scores apparaît dépendante à l'origine ethnique. ‐ Le cas pratique confirme nos résultats précédents obtenues cliniquement, c'est à dire que de nombreux signes faciaux ont été trouvés d'amplitude plus importante pour les hommes exposés à une pollution aérienne urbaine sévère en comparaison de ceux vivant dans une ville moins polluée. ‐ Les deux études ont démontré l'adéquation statistique entre le système automatique et les évaluations des experts et dermatologues. Pour certains signes, une certaine supériorité de système automatique a pu être observée vis‐à‐vis de l'évaluation des experts. Conclusion: A l'exception de quelques limitations mineures, le nouveau système de scorage automatique, basé sur l'IA, du visage des hommes – ne nécessitant aucune intervention humaine – fonctionne aussi bien que celui dédié aux femmes et toujours en parfaite adéquation avec les dermatologues. Pour des études épidémiologiques, ce système offre une approche rapide, aisée, confidentielle et d'un coût très abordable pour la détection et la quantification des signes faciaux masculins.